Advanced materials for enamel remineralization - Xu, Jiarong; Shi, Hui; Luo, Jun; Yao, Haiyan; Wang, Pei; Li, Zhihua; Wei, Junchao (Frontiers in Bioengineering and Biotechnology, 2022)
Dental caries, a chronic and irreversible disease caused by caries-causing bacteria, has been listed as one of the three major human diseases to be prevented and treated. Therefore, it is critical to effectively stop the development of enamel caries. Remineralization treatment can control the progression of caries by inhibiting and reversing enamel demineralization at an early stage. In this process, functional materials guide the deposition of minerals on the damaged enamel, and the structure and hardness of the enamel are then restored. These remineralization materials have great potential for clinical application. In this review, advanced materials for enamel remineralization were briefly summarized, furthermore, an outlook on the perspective of remineralization materials were addressed.